Fracture-controlled fluid transport supports microbial methane-oxidizing communities at Vestnesa Ridge - Yao, Haoyi; Hong, Wei-Li; Panieri, Giuliana; Sauer, Simone; Torres, Marta E.; Lehmann, Moritz F.; Gründger, Friederike; Niemann, Helge (Biogeosciences, 2019)
We report a rare observation of a mini-fracture in near-surface sediments (30 cm below the seafloor) visualized using a rotational scanning X-ray of a core recovered from the Lomvi pockmark, Vestnesa Ridge, west of Svalbard (1200 m water depth). Porewater geochemistry and lipid biomarker signatures revealed clear differences in the geochemical and biogeochemical regimes of this core compared with two additional unfractured cores recovered from pockmark sites at Vestnesa Ridge, which we attribute to differential methane transport mechanisms. In the sediment core featuring the shallow mini-fracture at pockmark Lomvi, we observed high concentrations of both methane and sulfate throughout the core in tandem with moderately elevated values for total alkalinity, 13C-depleted dissolved inorganic carbon (DIC), and 13C-depleted lipid biomarkers (diagnostic for the slow-growing microbial communities mediating the anaerobic oxidation of methane with sulfate – AOM). In a separate unfractured core, recovered from the same pockmark about 80 m away from the fractured core, we observed complete sulfate depletion in the top centimeters of the sediment and much more pronounced signatures of AOM than in the fractured core. Our data indicate a gas advection-dominated transport mode in both cores, facilitating methane migration into sulfate-rich surface sediments. However, the moderate expression of AOM signals suggest a rather recent onset of gas migration at the site of the fractured core, while the geochemical evidence for a well-established AOM community at the second coring site suggest that gas migration has been going on for a longer period of time. A third core recovered from another pockmark along the Vestnesa Ridge Lunde pockmark was dominated by diffusive transport with only weak geochemical and biogeochemical evidence for AOM. Our study highlights that advective fluid and gas transport supported by mini-fractures can be important in modulating methane dynamics in surface sediments.